Piezo1 senses hyphae and initiates host defense against pathogenic fungi - Yiran Shi; Bingying Yang; Yueyue Linghu; Yue Liu; Haoran Li; Yunzhi Xing; Binbin Wu; Yuting Gao; Liuqi Liao; Yi Zheng; Lei Pan; Xiufeng Sun; et al. (Cell Reports)
Summary: Candida albicans metamorphoses from benign yeast to a rigid hyphal, becoming an opportunistic pathogen in immunocompromised patients. The process by which immune cells discern fungal transformations remains elusive. Here, we report that the mechanosensitive ion channel Piezo1 is indispensable for recognizing fungal hyphae and triggering antifungal innate immune responses. Hyphae-triggered Piezo1 activation increased C-type lectin receptor (CLR) expression in innate immune cells by inducing the expression of CCAAT/enhancer-binding protein beta (C/EBPβ) via the Piezo1/Ca2+/calmodulin-dependent kinase (CaMK)/cAMP response element-binding protein (CREB) axis. In addition, Piezo1/CaMK signaling activated kinases nuclear Dbf2-related protein 1/2 (NDR1/2), which augmented NLRP3 inflammasome assembly and promoted hyphae-induced inflammation. Abolishing the yeast-to-hyphae transition dampens CLR expression and NLRP3 activation. Piezo1-deficient mice exhibit compromised clearance of C. albicans infection, whereas Piezo1 agonist amplifies C. albicans clearance. In addition, CaMK, CREB, or NDR1/2 inhibition exacerbates hyphae infections, such as Piezo1 deficiency. Therefore, we ascertain Piezo1-mediated mechanotransduction as vital for immune surveillance and control of hyphal C. albicans, heralding Piezo1 agonist as a potential remedy for fungal infections.